The Influence of Online EFL Learning Toward the Students' Motivation - Alma Isnaini Fachrunisa (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The objectives of this study aimed to find out the ways online EFL learning influences studentsâ€™ motivation, as well as the factors influence it. This research used qualitative approach. The researcher collected data by distributing questionnaires and conducted interviews. The population in this study is the second, fourth, and sixth students who experience online EFL learning to filled out the questionnaire. Further, interview was applied to three representative participants from each semester that had the lowest or highest motivation score according to the questionnaire results. The data finding showed that students are quite motivated by doing online EFL learning, both on intrinsic motivation and extrinsic motivation. The majority of students concur that online EFL learning is very helpful for learning languages, that utilizing it also helps students' English skills, and that the programs utilized by their instructors are also quite interesting and exciting.Keywords:Â Learning Motivation, Online EFL Learning